2015
DOI: 10.3109/10253890.2015.1053451
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmune mechanisms of stress: sex differences, developmental plasticity, and implications for pharmacotherapy of stress-related disease

Abstract: The last decade has witnessed profound growth in studies examining the role of fundamental neuroimmune processes as key mechanisms that might form a natural bridge between normal physiology and pathological outcomes. Rooted in core concepts from psychoneuroimmunology, this review utilizes a succinct, exemplar-driven approach of several model systems that contribute significantly to our knowledge of the mechanisms by which neuroimmune processes interact with stress physiology. Specifically, we review recent evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 149 publications
(200 reference statements)
1
52
0
Order By: Relevance
“…Indeed, sex differences in HPA axis responses are well precedented (for reviews, see Kudielka & Kirschbaum, 2005; Weinberg, Sliwowska, Lan, & Hellemans, 2008) and, based on the present findings, do not appear to be predictive of neuroimmune gene alterations produced by acute ethanol exposure. With that said, CORT and PROG responses to acute ethanol challenge provide an important physiological context to the cytokine alterations, as previous studies have demonstrated a key role for neuroendocrine hormones in the regulation of cytokines (see Deak et al, 2015 for review).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, sex differences in HPA axis responses are well precedented (for reviews, see Kudielka & Kirschbaum, 2005; Weinberg, Sliwowska, Lan, & Hellemans, 2008) and, based on the present findings, do not appear to be predictive of neuroimmune gene alterations produced by acute ethanol exposure. With that said, CORT and PROG responses to acute ethanol challenge provide an important physiological context to the cytokine alterations, as previous studies have demonstrated a key role for neuroendocrine hormones in the regulation of cytokines (see Deak et al, 2015 for review).…”
Section: Discussionmentioning
confidence: 99%
“…Not only is corticosterone a useful marker of sensitivity to ethanol (Glavas et al, 2007), but it also exerts a profound influence on neuroimmune gene expression in a variety of contexts (see Deak et al, 2015 for a recent review). In the current studies, ethanol-induced elevations in corticosterone were present after acute exposure, but have been shown to habituate with chronic (2 g/kg i.p.…”
Section: Discussionmentioning
confidence: 99%
“…Immune proteins are required for normal synaptic plasticity (O'Connor and Coogan, 1999; del Rey et al, 2013) and stress may influence memory via interactions with immune signaling (Deak et al, 2015; Vecchiarelli et al, 2015). Furthermore, activation of the peripheral immune system during illness or injury, and the resulting neuroimmune response (Figure 1), dramatically alters memory processes.…”
mentioning
confidence: 99%
“…There is growing evidence for a central role of immune cells and signaling in memory formation and its modulation (Donzis and Tronson, 2014;Haydon and Nedergaard, 2015;Wu et al, 2015). Immune proteins are required for normal synaptic plasticity (O'Connor and Coogan, 1999;del Rey et al, 2013), and stress may influence memory via interactions with immune signaling (Deak et al, 2015;Vecchiarelli et al, 2015). Furthermore, activation of the peripheral immune system during illness or injury, and the resulting neuroimmune response (Fig.…”
mentioning
confidence: 99%